The neural basis of self-ambivalence: an ERP study - Dian Chen; Ying Liu; Yulin Zhang; Yiting Guo (BMC Psychology)
Abstract The primary objective of this study was to investigate the neural basis of self-ambivalence, a phenomenon firmly established by behavioral research but whose underlying brain mechanisms have been less explored. Employing EEG methods and a modified self-reference paradigm, we analyzed event-related potentials using a linear mixed model to determine whether self-ambivalence processing exhibits a distinct neural representation. The results indicated that self-ambivalence processing primarily affected the late components (N2, N450, and P3), with N450 activation in the midline brain regions showing a significant positive correlation with scores on the Dialectical Self Scale. This finding suggests that individuals with higher levels of self-ambivalence may engage in more extensive processing of self-ambivalent information. The current study confirms the importance of the cortical midline in self-ambivalence and provides the first evidence of a distinct EEG representation of self-ambivalence processing. These findings contribute to our understanding of the neural mechanisms underlying self-ambivalence and highlight the potential role of individual differences in shaping the neural processing of self-ambivalent information.